Elaboración de un manual de gestión ambiental según la metodología de sistemas de gestión o integrados de acuerdo a la orma ISO 14001 para la empresa - Bernal Paredes, Freddy (2009)
The job(aim) consisted on elaborating an Environmental Management Handbook for Plastiempaques S.A. company, which is dedicated to make plastic products. The project scope was the plant production processes. The data collection was performed using workshops and interviews with employees, besides the information gathering company's environmental performance. The Handbook contains an Initial Environmental Review which evaluated the performance and the company's environmental commitments. In the second phase, it was developed the Planning that includes the Environmental Policy formulation and the review of the Environmental Legal Standards relevant to their production processes, objectives and targets were formulated based on the policy with their respective Environmental Management Programs to bring out. In the third part “implementation” which focuses on defining structures, responsibilities and control of productive operations. The Fourth part corresponded to the Test, which assesses compliance with the Procedures and Environmental Programs of the company. Finally we proceeded to the Management Review, which assesses compliance with the Environmental Goals and Management System.